Comparative study on lubrication properties of biodiesel and bio-lubricant trans-esterified from desert seed oil with conventional lubricants - Adeoti, M. O.; Jamiru, T.; Adegbola, T. A.; Abdullahi, M.; Sulaiman, I.; Aramide, B.P. (Frontiers in Chemical Engineering, 2024)
In recent years, there has been an increasing focus on renewable and biodegradable energy sources among lubricant manufacturers due to the environmental impacts and limited availability of fossilbased engine oils. Biomass sources present a cost-effective and eco-friendly alternative to traditional mineral oil sources. This study aims to produce and characterize biodiesel and biolubricant from desert date seed oil through transesterification. The result of the study was compared with the properties of conventional and commercial lubricants. The study employed transesterification to convert desert date seed oil into biodiesel and biolubricant. The produced biolubricant and biodiesel were characterized to determine their kinematic viscosity at 40°C, specific gravity, flash point, and pour point. These properties were then compared with those of other bio-lubricants and commercial base lubricants. For biodiesel, the yield was 56%, with a favorable acid value (0.98 mg KOH/g), iodine value (43.41 mg/g), and saponification value (197.4 mg KOH/g). Although, the specific gravity (1.876) was higher than ASTM standard. However, the flash point (112°C) and cloud point (11°C) were within acceptable ranges. The biolubricant produced from desert date oil showed promising results with a high kinematic viscosity of 67.54 mm²/s, a specific gravity of 1.876, a flash point of 120°C and a pour point (-5°C). These results obviously suggest the produced lubricant a suitable for automotive applications possessing good low-temperature performance. The flash point result and the physicochemical properties of the oil aligned well with industrial standards. The comparisons revealed that the produced biolubricant closely matched the properties of SAE VG 220 and SAE VG 40. The findings suggest that the biolubricant and biodiesel derived from desert date seed oil can serve as a viable substitute for petroleum-based lubricants in light gear applications and can be effectively used in two-stroke engines, providing a sustainable alternative to conventional lubricants.